Hubungan Jenis Kelamin dan Asupan Purin dengan Kadar Asam Urat pada Lansia di Posyandu Peduli Insani Mendungan Desa Pabelan Kecamatan Kartasura Kabupaten Sukoharjo - , Rini; , Setyaningrum Rahmawaty, A.,M.Kes.,PhD; , dr. Listiana Dharmawati,. M.Si (2017)
DEPARTMENT OF NUTRITION SCIENCE FACULTY OF HEALTY SCIENCE UNIVERSITAS MUHAMMADIYAH SURAKARTA BACHELOR THESIS ABSTRACTS Rini J 310 120 0004 THE RELATIONSHIP OF GENDER AND PURINE INTAKE WITH THE LEVELS OF URIC ACID OF ELDERLY IN POSYANDU PEDULI INSANI MENDUNGAN PABELAN KARTASURA SUKOHARJO Background : Gender may effect the level of uric acid due to the influence of the estrogen hormone. High purine intake can increase the uric acid levels since the final product of purine metabolism is in the form of uric acid catalized by the enzyme xanthine oxidase. Objective : To determine the relationship of gender and purine intake with the uric acid levels of elderly at Posyandu Peduli Insani Mendungan Pabelan Kartasura Sukoharjo. Research Methods : The research was an observasional study with cross sectional approach. Sixty-seven elderly were recruited using Simple Random Sampling technique. A questionnaire was used to measure respondent characteristics. The data of purine intake were obtained using semi-quantitative Food Frequency Questionnaire and uric acid levels were analyzed by spectrophotometer using venous blood. The relationship between gender and uric acid levels using Chi Square test, while purine intake and uric acid levels using Pearson Product Moment test. Results : Twenty-seven (96.40%) female elderly have high uric acid levels and 26 (92.90%) elderly have high purine intake with high uric acid levels. The result of correlation test indicated that there is a relationship between gender and purine intake and the uric acid levels of elderly,with p value 0.003 and 0.001 respectively. Conclusions : Gender and purine intake are related to the uric acid levels of elderly at Posyandu Peduli Insani Mendungan Pabelan KartasuraSukoharjo. Keywords : Blood uric acid, Elderly, Gender,Purine intake Bibliography :40 (2002 - 2015)